Penerapan Transaksi Jual Beli Pakaian Bekas Impor di Indonesia Ditinjau dari Pasal 47 Ayat (1) Undang-Undang Nomor 7 Tahun 2014 Tentang Perdagangan - Haris Sanjaya, Umar; Hernan Saputra, Adnan Noor (Veteran Law Review, 2024)
This research discusses the application of second-hand imported clothing trading transactions in Indonesia that are regulated by Article 47 Paragraph (1) of Law Number 7 of 2014 concerning Trade. The issue discussed in this thesis is to determine how the application of Article 47 Paragraph (1) of Law Number 7 of 2014 concerning Trade regulates the trading transactions of second-hand imported clothing in Indonesia and what legal impacts arise from the trading of second-hand imported clothing in Indonesia on the domestic clothing industry. This is analyzed in detail based on legal position, legal consequences, and seller responsibilities in trading second-hand imported clothing. The method used is normative juridical research by collecting data from primary and secondary legal materials such as legislation, books, journals, and previous research results that are relevant to the research discussion. The results of this research indicate that trading of imported second-hand clothing in Indonesia must comply with the regulations set by the law, and trading of second-hand imported clothing that does not comply with these regulations may result in sanctions such as import restrictions or even business closure. Furthermore, strict supervision is necessary from the relevant authority to limit the trading of second-hand imported clothing in Indonesia, and sellers must be cautious in conducting transactions in order to avoid legal sanctions.